Quality-Based Educational Personnel Management in Improving Educational Services at Muhammadiyah 7 Elementary School, Bandung City - Maeswaty, Agnes Devita; Hasanah, Enung; Santosa, Achadi Budi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Educational staff management is a crucial factor in supporting the achievement of quality educational services in schools. SD Muhammadiyah 7 Kota Bandung, as a private educational institution, strives to implement quality-based management to enhance the performance of its educational staff and the services provided to students. This study aims to analyze and describe Quality-Based Educational Staff Management in Improving Educational Services at SD Muhammadiyah 7 Kota Bandung. This research employs a qualitative method, conducted at SD Muhammadiyah 7 Kota Bandung. Data collection techniques include interviews, observation, and documentation. In-depth interviews were conducted with the vice principal for human resources, the vice principal for public relations, educational staff members, and the school committee. Data analysis was supported by the use of Atlas.ti 9 software to reveal theoretical frameworks and field findings. The research results show that quality-based management of educational staff has been implemented through five main aspects: (1) systematic planning of educational staff needs through competency and qualification mapping; (2) competency development and improvement through training, performance evaluation, and active involvement in school programs; (3) efficient and responsive educational services supported by an integrated information and service system (OSS); (4) periodic evaluation and quality assurance used as a basis for policy making; and (5) communicative and collaborative leadership between schools, teachers, and educational staff. With the optimization of training programs, strengthening of data-based evaluation systems, and developing cross-work unit collaboration, it is hoped that the quality of educational services will be maintained and improved sustainably.